Preliminary analyses of vernacular earthen architecture in the gardens of al-‘Ūla oasis (Saudi Arabia) - Clauss-Balty, Pascale; Kanhoush, Yasmin; Ben Bader, Sarra; Charbonnier, Julien (Proceedings of the Seminar for Arabian Studies, 2023)
The palm grove of al-‘Ūla oasis (KSA) contains, beside plots solely dedicated to agriculture, hundreds of complexes, called “farms”, spatially divided into two groups and established, for at least for one of them, after the early twentieth century AD. These farms and their components are subject to an in-depth study conducted within the AlUla Cultural Oasis Project (UCOP) led by Archaïos, funded and steered by the French Agency for AlUla Development (AFALULA) on behalf of the Royal Commission for AlUla (RCU). All built with local materials, mainly earth, these farms reflect the ingenuity of Arabian vernacular architecture and its evolution. In this present paper, construction techniques used within the oasis farms will first be discussed. Secondly, focus will be on farm dwellings: al-‘Ūla oasis houses present a range of possibilities, from single-cell to multi-cell buildings, with interior and exterior courtyards, terraces and upper floors. The examination of a large number of these dwellings allowed us to identify the function of certain spaces and to consider the daily life and the societal structuring of the inhabitants of al-‘Ūla oasis who settled in their palm grove until the 1980s. This research aims to fill a major gap: at the scale of Saudi Arabia, rural buildings have never been subject to comprehensive studies while they are currently threatened by development in many places.